2019
DOI: 10.1037/spq0000277
|View full text |Cite
|
Sign up to set email alerts
|

Predicting reading comprehension in young children with autism spectrum disorder.

Abstract: Relationships between early literacy measures (i.e., curriculum-based measurement) and advanced literacy measures (i.e., reading comprehension) were examined in young children with autism spectrum disorders (ASDs). Participants in this study were 167 children between the ages of 4 and 7 years ( = 5 years 8 months), who were assessed at 2 time points during 1 school year. Results indicated that, compared to other measures of early literacy skills, curriculum-based measurements (CBMs) accurately assessed skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…In a substantial proportion of cases, this sequence is coupled with an early interest in written code, with decoding skills superior to comprehension in the hyperlexic period. In most cases, it predicts catching up in reading comprehension after five years of age [99]. The nature of the oral utterances or reading prerequisites that the child demonstrates during this sequence supports the idea that oral and written language are not primarily learned in a communicative way in autism.…”
Section: Atypical Language Progressionsupporting
confidence: 54%
“…In a substantial proportion of cases, this sequence is coupled with an early interest in written code, with decoding skills superior to comprehension in the hyperlexic period. In most cases, it predicts catching up in reading comprehension after five years of age [99]. The nature of the oral utterances or reading prerequisites that the child demonstrates during this sequence supports the idea that oral and written language are not primarily learned in a communicative way in autism.…”
Section: Atypical Language Progressionsupporting
confidence: 54%
“…In a substantial proportion of cases, this sequence is coupled with an early interest in written code with decoding skills superior to comprehension in the hyperlexic period. In most cases, it predicts the catching-up in reading comprehension after five years of age [98]. The nature of the oral utterances or reading prerequisites that a child demonstrates during this sequence supports the idea that oral and written language are not primarily learned in a communicative way in autism.…”
Section: Atypical Language Progressionmentioning
confidence: 54%
“…Increased hyperlexic traits were also associated with more other-directed behaviors in social interaction and imagination in the ADOS as well as better imitation skills in the PEP-3. The ASD+eHPL group had a higher hyperlexic trait score than the age-matched TD group, confirming that early literacy-related interest and ability occurs primarily in ASD compared to typical development [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 90%
“…Letter identification appears to be a prerequisite to this principle and is a key skill in inducing subsequent word decoding. Regarding the emergence of letter naming, it has been shown that children with ASD between 4 and 7 years old tend to name more letters than their TD peers at the same age [ 31 , 32 ], but this gap disappears around first grade [ 31 ]. Furthermore, children with ASD and hyperlexia have better letter naming skills than their ASD as well as TD peers [ 33 ].…”
Section: Introductionmentioning
confidence: 99%